Anonymous
Anonymous asked in Science & MathematicsMathematics · 5 years ago

exponentials and logarithms?

f(x)=Axe^-kx

find the value of f(4).

give answer as fraction and a decimal. please show all work.

2 Answers

Relevance
  • Huh
    Lv 6
    5 years ago
    Favorite Answer

    Easy! Just let x = 4, as instructed.

    Equation 1: f(4) = A(4) * e^(-4 * k)

    No amount of guessing will tell me what A or k is.

    -----------

    f(1) = 5, okay then:

    Equation 2: 5 = A * (1) * e^(-k)

    f(2) = 7. Okay, then:

    Equation 3: 7 = A * (2) * e^(-2k)

    Divide equation 2 over equation 3 to eliminate A to 1.

    5 / 7= [A * (1) * e^(-k)] / [A * (2) * e^(-2k)]

    5 / 7 = ((e^(-k)) / ((2 * e^(-2k)

    Multiply out the 2, it's in the way of my reasoning.

    10 / 7 = [e^(-1 * k)] / [e^(-2 * k)

    (10 / 7) = { [e^(k)]^(-1) } / { [e^(k)]^(-2) }

    Let e^k = c. I chose c because it's my jam.

    (10 / 7) = [c^(-1)] / [c^(-2)]

    (10 / 7) = c^[-1 - (-2)] >>> you do understand this, right?

    (10 / 7) = c^(1) = c

    Undo the substitution:

    10 / 7 = e^k

    Take the natural logarithm of both sides of the equation because Euler's number.

    ln(10 / 7) = k * ln(e), as ln(e) = 1.

    ln(10 / 7) = k

    ln(10) - ln(7) = k

    0.3567 approx. = k

    -----------

    Find A from either equation 2 or equation 3:

    5 = A * e^(-k)

    Divide both sides by A:

    5 / A = e^(-1 * k)

    5 / A = [(e)^k]^(-1)

    5 / A = 1 / e^(k)

    Cross multiply:

    5 * e^(k) = A(1)

    And what was k?

    5 * e^[ln(10 / 7)] = A

    That e raised to the log base e, totally cancels that logarithm bro, or sis.

    5 * (10 / 7) = A

    50 / 7 = A

    --------

    Solution set: A = 50 / 7, and k = ln(10 / 7)

    ---------

    Finally, back to the main equation for the main event!!!!!!!!!!!!!!!!!!!! The moment that you've all been waiting for.

    f(4) = A(4) * e^(-4 * k)

    f(4) = (50 / 7) * (4) * e^[-4 * ln(10 / 7)]

    Kick the -4 into the natural logarithm as a power :

    f(4) = (200 / 7) * e^{ [ln(10 / 7)^(-4)] }

    The natural logarithm gets destroyed:

    f(4) = (200 / 7) * (10 / 7)^(-4)

    f(4) = (200 / 7) * (7 / 10)^4

    f(4) = (200 / 7) * (7^4 / 10^4)

    f(4) = (200 / 7) * (2401 / 10000)

    f(4) = (2401 / 7) * (200 / 10000)

    f(4) = 343 * (1 / 50)

    f(4) = 343 / 50 = 6.86

    • Login to reply the answers
  • 5 years ago

    f(4) = 4A e^(-4k)

    You can't simplify that farther without knowing values for A and k.

    • Login to reply the answers
Still have questions? Get your answers by asking now.